The The Role of Customer Relationship Management in Customer Retention: Case Study for Ambon Traditional Restaurants - Lesbassa, Ricky Kurniawan; Lewerissa, Erlina; Betoky, Markus Imanuel; Aribowo, Agus (Manunggal Halim Jaya, 2026)
The culinary industry in Indonesia continues to grow, with restaurants serving regional specialties such as Ambon cuisine. Building and maintaining long-term customer relationships has become an essential strategy for enhancing loyalty and business sustainability. This study aims to analyze the effectiveness of Customer Relationship Management (CRM) on customer retention in Ambon specialty restaurants. The research method employed is a literature study with a descriptive-analytical approach. The findings indicate that effective CRM implementation can enhance customer retention through service personalization, loyalty programs, and continuous communication. CRM components such as personalized service, effective communication, and loyalty programs have been proven to increase customer satisfaction and the likelihood of repeat purchase. The study concludes that consistently implemented CRM strategies can be a key factor in retaining customers and improving restaurants' competitiveness.